2012
DOI: 10.1016/j.spen.2012.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus and the Central Nervous System

Abstract: The pandemic of HIV/AIDS continues to grow daily. Incident cases among women, intravenous drug users and ethnic minorities comprise the fastest growing segment of the HIV-infected population, and the number of HIV-infected individuals over the age of 50 is growing rapidly. Today, the central nervous system and the immune system are seen as main targets of HIV infection. Significant progress in the knowledge and treatment of AIDS has been obtained in recent years. The neurological manifestations directly relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…HIV has been shown to infect the cochlea (Michaels et al 1994; Pappas et al 1994; Soucek et al 1996). The central nervous system can serve as a reservoir for HIV (Mirza et al 2012) so central auditory pathways could also be affected by HIV, which could lead to central auditory processing deficits (Maro et al 2014), or effects on efferent pathways from the brainstem and other areas to the cochlea. In addition, the presence of enhanced generalized inflammation in both untreated as well as treated HIV-infected individuals may contribute to auditory deficits if this inflammation were in the cochlea or auditory pathways.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HIV has been shown to infect the cochlea (Michaels et al 1994; Pappas et al 1994; Soucek et al 1996). The central nervous system can serve as a reservoir for HIV (Mirza et al 2012) so central auditory pathways could also be affected by HIV, which could lead to central auditory processing deficits (Maro et al 2014), or effects on efferent pathways from the brainstem and other areas to the cochlea. In addition, the presence of enhanced generalized inflammation in both untreated as well as treated HIV-infected individuals may contribute to auditory deficits if this inflammation were in the cochlea or auditory pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Even in the treated state, substantial concern exists for continued central nervous system (CNS) involvement given its compartmental nature and differential pharmacokinetic distribution of antiretroviral drugs. Neurocognitive deficits are still seen in HIV+ individuals despite active antiretroviral therapy (ART) (Mirza and Rathore 2012). Taken together, existing data suggest multiple potential ways that HIV could affect the hearing system.…”
Section: Introductionmentioning
confidence: 99%
“…Even in the treated state, substantial concern exists for continued CNS involvement given its compartmental nature and differential pharmacokinetic distribution of antiretrovirals (ARVs). Neurocognitive deficits are still seen in HIV+ individuals despite active antiretroviral therapy (Mirza and Rathore 2012). Taken together, existing data suggest multiple potential ways that HIV could affect hearing, but to date, no large scale study has shown which of these potential causes predominates or how frequently hearing problems occur in HIV+ individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages and dendritic cells are also targets of HIV infection. [42][43] The HIV/AIDS is a challenge for healthcare providers due to lack of resources, limited infrastructure and low socioeconomic status and educational level of most patients. [44][45] Thus, we emphasize the importance of promoting health, which is understood as a process of empowerment of individuals and the community to work on improving the quality of life and health.…”
Section: Discussionmentioning
confidence: 99%